A pécsi Fabrica - Margócsy, Dániel; Somos, Márk; Joffe, Stephen N. (Per Aspera ad Astra, 2018)
This article provides information on a copy of the 1543 edition of Andreas Vesalius’ De humani corporis fabrica, preserved at the Klimo Library of the University of Pécs. This copy helps us understand the complex reception of Andreas Vesalius’ groundbreaking anatomical work amongst Lutherans in the sixteenth century, and shows the importance of the University of Wittenberg, and Philipp Melanchthon, in shaping anatomical knowledge in Germanic lands. It also documents the tight connections between Wittenberg and the University of Padova, and reveals the continuing importance of Ancient learning for physicians working in the wake of the Vesalian revolution.